Ethnic identity in English language textbooks: Considerations for a multicultural society / Puspalata C Suppiah and Ramesh Nair - C Suppiah, Puspalata; Nair, Ramesh (Penerbit UiTM (UiTM Press), 2016)
There is evidence to suggest that young children more readily absorb the subtle messages that are encoded in any type of text and talk, and what they take away from these texts contributes in helping them develop their own identity in relation to their role in society. In this paper, we examine the construction of ethnic identity in a selection of English language textbooks targeted at young Malaysian children in primary schools. Based on a content analysis of visual and verbal language in two Primary Three English language textbooks, we report on the encoded messages that are transmitted to young Malaysian children about their place in society. The findings reveal significant imbalances in the way characters of different ethnic backgrounds are represented. This imbalance is a cause for concern as the message conveyed to young Malaysian children could be potentially damaging.